The block by block method with Romberg quadrature for solving nonlinear Volterra integral equations on the large intervals - Katani, R.; Shahmorad, S. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We investigate the numerical solution of nonlinear Volterra integral equations by block by block method, which is useful specially for solving integral equations on large-size intervals.A convergence theorem is proved that shows that the method has at least sixth order of convergence. Finally, the performance of the method is illustrated by some numerical examples.